Aptamers in Bordeaux, 24–25 June 2016 - Jean-Jacques Toulmé (Pharmaceuticals, 2017)
The symposium covered the many different aspects of the selection and the characterization of aptamers as well as their application in analytical, diagnostic and therapeutic areas. Natural and artificial riboswitches were discussed. Recent advances for the design of mutated polymerases and of chemically modified nucleic acid bases that provide aptamers with new properties were presented. The power of aptamer platforms for multiplex analysis of biomarkers of major human diseases was described. The potential of aptamers for the treatment of cancer or cardiovascular diseases was also presented. Brief summaries of the lectures presented during the symposium are given in this report. A second edition of “Aptamers in Bordeaux” will take place on September 2017 (http://www.aptamers-in-bordeaux.com/).